2019
DOI: 10.1177/0021998319857116
|View full text |Cite
|
Sign up to set email alerts
|

Nonwoven polyester interleaving for toughness enhancement in composites

Abstract: Various researchers have developed techniques to control delamination in laminated structures. One of these techniques is “interleaving,” adding high toughness material to key interfaces in a laminate. This paper studies using polyester veil as a low-cost interleaf alternative to other materials and focuses on a nonwoven, polyester spunbond material. Two different interleaf thicknesses, 0.18 mm and 0.74 mm, are primarily used. In addition, fine 4 g/m2 polyester was also compared. Carbon/epoxy composites are ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…41 Similarly, nylon 6,6 nonwoven fabric has been reported to increase the Mode-I initiation and propagation fracture toughness of carbon fiber epoxy composites by 34% and 156%, respectively. 28 Interleaves made of high toughness materials can contribute to enhance interlaminar toughness of the composite laminates, 37 therefore, selection of the interleaves made of appropriate material is important. 41 Ultra-High Molecular Weight Polyethylene (UHMWPE) or high-performance polyethylene (HPPE) fibers possess attractive properties, such as, high specific strength and modulus, low density, high elongation and energy absorption characteristics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Similarly, nylon 6,6 nonwoven fabric has been reported to increase the Mode-I initiation and propagation fracture toughness of carbon fiber epoxy composites by 34% and 156%, respectively. 28 Interleaves made of high toughness materials can contribute to enhance interlaminar toughness of the composite laminates, 37 therefore, selection of the interleaves made of appropriate material is important. 41 Ultra-High Molecular Weight Polyethylene (UHMWPE) or high-performance polyethylene (HPPE) fibers possess attractive properties, such as, high specific strength and modulus, low density, high elongation and energy absorption characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tensile strength of the composites containing aramid interleaves was lower than that of control samples due to reduced volume fraction of the carbon fibers. Gheryani et al 37 investigated the effect of polyester nonwoven interleaves on fracture toughness of woven carbon fabric epoxy composites and found that Mode‐I and Mode‐II fracture toughness was increased. The increase in Mode‐I fracture toughness was significant compared with Mode‐II fracture toughness.…”
Section: Introductionmentioning
confidence: 99%
“…in [5] results of experimental studies are presented, where the porosity of the spunbonded fabrics in composites is analyzed. The authors of [6] deal also with spunbonded nonwovens in composites, but focuses on their application as interleaves and the enhanced resulting toughness of the composite. In the application of spubonded nonwovens for filter media, the bicomponent nonwovens in particular play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Effect of the input material parameters on the fiber laydown characteristics: the effect of E modulus (first row, left figure) and the effect the density (first row, right figure) are on the same order of magnitude, while the effect of the line density is approximately 10 times bigger than the effect of E modulus and density (see second row, center figure).TA B L E 1 Average elasticity measures (dimensionless quantities) computed due to equation(6) …”
mentioning
confidence: 97%
See 1 more Smart Citation